2014
DOI: 10.1371/journal.pone.0106333
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Childhood Body Size, Composition, Blood Pressure and Adult Cardiac Structure: The Fels Longitudinal Study

Abstract: ObjectivesTo determine whether childhood body size, composition and blood pressure are associated with adult cardiac structure by estimating childhood “age of divergence.”Methods385 female and 312 male participants in the Fels Longitudinal Study had echocardiographic measurements of left ventricular mass, relative wall thickness, and interventricular septal thickness. Also available were anthropometric measurements of body mass index, waist circumference, percentage body fat, fat free mass, total body fat, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Although there are insufficient data demonstrating that LVH in children persists into adulthood, there is evidence that childhood hypertension and obesity are associated with adult LVH. 24,25 It seems likely that without proper, timely intervention, children with LVH will become adults with LVH and its attendant risks. Our study confirms that such children are commonly seen in pediatric practice.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are insufficient data demonstrating that LVH in children persists into adulthood, there is evidence that childhood hypertension and obesity are associated with adult LVH. 24,25 It seems likely that without proper, timely intervention, children with LVH will become adults with LVH and its attendant risks. Our study confirms that such children are commonly seen in pediatric practice.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately two out of three Americans adults and one in three children are classified as overweight or obese . Chronic diseases such as metabolic syndrome, cardiovascular disease and hypertension, along with mortality in adulthood, are serious health issues that arise from being overweight and obese in childhood . The appearance of chronic diseases during childhood, as a consequence of obesity, is also a major public health concern in the USA .…”
Section: Introductionmentioning
confidence: 99%
“…Extending this observation to childhood, investigators from the Bogalusa Heart Study found that children with elevated BMI and elevated BP developed higher LVM in adulthood, but obesity was a stronger predictor (27). Similarly, investigators from the Fels longitudinal study found childhood BMI, but not fat mass or other adiposity indices, predicted future LVH (28). In each of these studies, BMI was a stronger predictor of future LVH than was BP.…”
Section: Discussionmentioning
confidence: 98%
“…LVH may be related to duration of exposure to hypertension (2628). Metanalyses show higher LVM values in hypertensive versus normotensive patients (29).…”
Section: Discussionmentioning
confidence: 99%